ANALISIS SISTEM INFORMASI YANG ADA PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN LAMPUNG UTARA - Marini; Roni Prayoga; Umi Rojiati (Komsospol, 2023)
The system can be defined as an organized component or variable that interacts with each other to carry out the same goal, resulting in input, output processing. Analysis of Information Systems at Diskominfo North Lampung is part of the use of developing a system, especially Diskominfo North Lampung has four main areas, namely, E-government, Statistics, coding, and infocomm, all of which are interrelated, the analysis is carried out using interviews and direct observation methods, The purpose of this analysis is to determine the performance of information systems in each field in Diskominfo North Lampung, especially in conveying information. As a result of these observations, there are several things that must be addressed, ranging from manual archiving which should be converted to digital, the delivery of information should follow media trends and submission of problems in the scope of the website. From the analysis carried out, it produces an output in the form of advice on the livelihood of information media in accordance with trends and prototypes of the Appoinmen system that will be used as a means of consultation about website problems within the North Lampung agency with the instruments used Flowcard, user and admin data, and the figma application UI/UX design software Appointment.